Hungarian Monitoring, 21 May 1989 . [Magyar rádiófigyelő], 1989. május 21 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Events in China - Miklós Németh's trip to Prague concerning Gabčíkovo-Nagymaros affair - Attempted putsch in Ethiopia - Polish election campaigns Domestic Affairs: - Hungarian Socialist Workers' Party (MSZMP) reform circles hold national talks in Szeged - Mátyás Szűrös's takes stance in favor of full legal and political rehabilitation of Imre Nagy - Cardinal László Paskai's Transcarpathian schedule - President of the Republic of Cyprus arrived in Hungary - Memorial visit to Don River planned Külpolitika: - A kínai események - Németh Miklós prágai útja - Bős-Nagymaros ügyében - Etiópiában puccsot kíséreltek meg - A lengyelországi választási kampány Belpolitika: - Az MSZMP reformköreinek szegedi országos tanácskozása - Szűrös Mátyás állást foglalt NAGY Imre teljes jogi - És politikai rehabilitálása mellett - Paskai László bíboros kárpátaljai programja - Hazánkba érkezett a Ciprusi Köztársaság elnöke - Doni emlék utat szerveznek